2022
DOI: 10.1590/1806-9282.20220200
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of COVID-19 patients assisted by intensivists and nonintensivists

Abstract: This observational study included adult patients with COVID-19 admitted to the ICU of Hospital Independence. Inclusion criteria were 18 years of age or older. There were no exclusion criteria. The Research Ethics Committee approved the study at our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(27 reference statements)
2
1
1
Order By: Relevance
“…The duration of the symptoms before admission to the hospital did not have an influence on the severity of the disease, which is contrary to the results of Loss SH et al [18] and Stojanovic M et al [19]. Our results can be explained by the fact that some of our patients were initially treated at home.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The duration of the symptoms before admission to the hospital did not have an influence on the severity of the disease, which is contrary to the results of Loss SH et al [18] and Stojanovic M et al [19]. Our results can be explained by the fact that some of our patients were initially treated at home.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results show that hypertension is more frequent in patients with severe disease, which is in agreement with the results of Allwood BW et al [20]. In contrast to Los et al [18], our results show that diabetes and chronic obstructive pulmonary disease did not have a statistically significant difference between the two groups. Although in our study diabetes did not prove to be a statistically significant comorbidity, we note that patients who had significantly higher glucose values at admission had more severe clinical conditions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Symptomatic COVID-19 patients typically present with respiratory syndrome, with fever and cough being commonly recorded [ 40 , 41 ]. According to a study conducted in Wuhan, China, involving 99 patients, the most prevalent reported symptoms were fever (83%), cough (82%), shortness of breath (31%), muscle ache (11%), confusion (9%), and headache (8%).…”
Section: Clinical Presentation Of Covid-19mentioning
confidence: 99%